Prince Boun Oum and the March 24, 1945 Treaty: A Possibility of Independent Champassak Following WW II - Kantala, Preeyaporn (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2021)
This article is part of the author’s ongoing study of Champassak and the formation of the new Lao state, with the aim of understanding Champassak’s dubious standing within Lao state, Siam, French Indochina, and even its self-image. In terms of historical methodology, the author discusses the treaty reached between Prince Boun Oum and Charles de Gaulle’s provisional government on March 24, 1945, which promised independence and membership in the French Union after WWII. Although Prince Boun Oum’s ambitious goal of independence for Champassak failed, this situation could be viewed as another form of the Lao state that was overlooked after Lao independence. Finally, the Champassak case is relevant to the debate about the current existence of a nation-state in this region and ethnic nationalism.